A rare neuromyelitis optica mimic: Primary CNS histiocytic sarcoma. (September 2022) - Rogawski, David S; Nirschl, Jeffrey J; McDonald, Jamie; Nie, Esther; Schwartz, Nicholas U; Vogel, Hannes; Scott, Brian J; Gold, Carl A; Kipp, Lucas B
Primary central nervous system (CNS) histiocytic sarcoma is a rare hematolymphoid malignancy with features of mature histiocytes and carries a poor prognosis. We describe a unique case in which a 50-year-old woman presented with recurrent acute brainstem syndrome, area postrema syndrome, and myelitis with corresponding magnetic resonance imaging (MRI) lesions meeting diagnostic criteria for seronegative neuromyelitis optica spectrum disorder (NMOSD). Despite initial improvement with steroids and plasma exchange, she experienced recurrent symptoms over 10 months referable to new and persistently enhancing lesions. At autopsy, neuropathology revealed a diffusely infiltrative primary CNS histiocytic sarcoma. This case represents a rare clinicoradiologic mimic of NMOSD, underscoring the importance of evaluation for infiltrative diseases in cases of atypical seronegative NMOSD.